Hypervalent Iodine Mediated Efficient Solvent-Free Regioselective Halogenation and Thiocyanation of Fused N-Heterocycles - Indukuri, Divakar Reddy; Potuganti, Gal Reddy; Alla, Manjula (Synlett, 2019)
A facile, rapid, metal-free regioselective halogenation and thiocyanation of imidazo[1,2-a]pyridine/pyrimidine heterocycles has been achieved under solvent-free reaction conditions. Halogenations and thiocyanation of the heterocycles could be accomplished by simple grinding of reactants and hypervalent iodine reagents with the corresponding alkali metal or ammonium salts. The method has been extrapolated to a cleaner synthesis of brominated imidazo[1,2-a]pyridine/pyrimidine derivatives, starting from the corresponding heterocyclic amines and substituted α-bromoketones, utilising HBr generated in situ as the source of bromine.
Keywords: solvent free; grinding; regioselective substitution; in situ bromination; atom economy